Pengaruh Pola Gaya Hidup Nasabah Terhadap Pengguna Aplikasi Mobile Banking di Kudus - Hardiyanti Hardiyanti (ITB AAS INDONESIA Surakarta, 2022)
Over the past two years since the Covid-19 pandemic in Indonesia, all business trends have implemented information system discipline by maximizing the use of Mobile Banking applications. This trend focuses on providing financial banking services using Android devices and is a major transaction for today's diverse everyday needs. This study aims to clarify the importance of mobile banking applications in the kudu banking sector. The data was collected using questionnaires distributed to 300 customers from several Islamic banks in Kudoz. The results showed that there was no statistically significant difference between user and non-user lifestyle patterns in mobile banking applications. However, users' lifestyle patterns have some common themes. Fashion, leadership, family awareness, health awareness, negligence, public awareness, and usefulness all have a significant impact on mobile application users, but cost awareness is where users use mobile banking applications. It does not have a significant impact on the methodology.